A meta-analysis of the clinical efficacy of Tanreqing injection combined with antibiotics vs antibiotics alone for treating pulmonary infection secondary to intracerebral hemorrhage. Issue 11 (19th March 2021) - Zhou, Dongrui; Xie, Liandi; Shi, Xiaowei; Liu, Fengzhi; Wu, Shuang; Zhang, Shuangshuang; Liu, Ruijia; Chang, Jingling; Zhu, Lingqun
Abstract: Background: Pulmonary infection is the most common complication to develop after intracerebral hemorrhage (ICH). Antibiotics have certain limitations when used to treat pulmonary infection, while Tanreqing injection (TRQI) is extensively used to treat pulmonary infection as an adjuvant to antibiotics. The aim of this meta-analysis was to investigate the clinical efficacy of TRQI for the treatment of lung infection secondary to ICH. Methods: Randomized controlled trials (RCTs) assessing the combination of TRQI and antibiotics compared to antibiotics alone for pulmonary infection after ICH were comprehensively searched for in 7 electronic databases from their establishment to August 2020. Two independent researchers conducted the literature retrieval, screening, and data extraction. The assessment tool of Cochrane risk of bias and Review Manager 5.3 software were applied to assess the methodological quality and analyze the data, respectively. Results: Seventeen RCTs involving 1122 patients with pulmonary infection after ICH were included. Compared to antibiotics alone, the combination treatment enhanced the clinical effective rate, shortened the hospital stay, reduced the white blood cell, procalcitonin, and C-reactive protein levels, ameliorated the times to the resolution of fever, cough, and lung rales, and increased the oxygenation index. The evidence indicated that TRQI combined with antibiotics caused no adverse reactions. Conclusions: Our study showed that the combination of TRQI and antibiotics was effective for treating pulmonary infection after ICH. However, high-quality multicenter RCTs are needed to further verify the clinical efficacy of TRQI due to the publication bias and the low methodological quality of the included RCTs.